THE EFFECT OF BUSUU APPLICATION ON STUDENTS VOCABULARY MASTERY (A QUASI-EXPERIMENTAL STUDY OF SEVENTH GRADE STUDENTS AT MADRASAH TSANAWIYAH NUR RAHMA IN BENGKULU CITY) - Irin Sugia; Nadrah; Febriani, Hanura (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of using the Busuu application on English vocabulary mastery of seventh-grade students at Madrasah Tsanawiyah Nur Rahma in Bengkulu City. The research was motivated by the dominance of conventional teaching methods that led to low student motivation and passive participation in vocabulary learning. A quantitative approach with a quasi-experimental design was employed, involving seventh-grade Makkah as the experimental class and seventh-grade Madinah as the control class. The sample consisted of 29 students selected using total sampling technique. Data were collected through pre-test and post-test, then analyzed using Shapiro-Wilk normality test, Levene's homogeneity test, and Independent Samples t-test. The results showed that the post-test scores of the experimental class were significantly higher than those of the control class. The Independent Samples t-test yielded a t-value of 4.281 with a significance value of 0.000 (p < 0.05), indicating a significant difference between the two groups after the treatment. These findings demonstrate that the use of the Busuu application is effective in improving students' English vocabulary mastery. Based on the results, it can be concluded that the Busuu application has a significant effect on the English vocabulary mastery of seventh-grade students at Madrasah Tsanawiyah Nur Rahma in Bengkulu City. Therefore, the Busuu application can be used as Mobile-Assisted Language Learning (MALL)-based instructional media to support English vocabulary learning.